TRANSFORMASI VAPE DI RUANG SOSIAL: DARI TEKNOLOGI MEDIS KE MODE (SEBUAH KAJIAN DENGAN PERPEKTIF SOCIAL CONSTRUCTION OF TECHNOLOGY) - Febriansyah, Febriansyah (Universitas Islam Malang, 2022)
Vape or e-cigarettes emerged as a medical technology to help heavy smokers quit smoking or get rid of their addiction to tobacco cigarettes since tobacco cigarettes contain harmful substances that can cause many deadly diseases. In its development, vaping has transformed into a popular product which considered as a fashion or part of the lifestyle of young people. How did it happen? This conceptual article will answer this problem by using the desk study method and the Social Construction of Technology (SCOT) theory. This article finds that the relevant society or social group strongly influences the transformation or evolution of vaping. Vaping is interpreted as a fashion by the relevant community or social group. This interpretation continues to be negotiated in the social sphere so that some groups define vaping as a smoking technology in the future when tobacco cigarettes will be replaced by it. The author also sees the influence of consumerism culture under neoliberalism, which is the context in the construction of vapes.